2022
DOI: 10.1139/apnm-2022-0263
|View full text |Cite
|
Sign up to set email alerts
|

Higher- and lower-load resistance exercise training induce load-specific local muscle endurance changes in young women: a randomised trial

Abstract: The effect of resistance training with higher- and lower-loads on muscle mass and strength has been extensively studied while changes in muscle endurance have received less attention. This trial aimed to assess the effect of training load on absolute (AME) and relative muscle endurance (RME). Sixteen untrained women (22.7±3.3 yr: mean ± SD) had one arm and leg randomly assigned to train with higher-loads (HL; 80-90% 1RM), and the contralateral limbs trained with lower-loads (LL; 30-50% 1RM) thrice weekly to vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Future research might also use randomized intervention designs to determine the extent to which strength preservation can be improved with training. Such research might identify exercise regimens that are most effective at improving tolerance to fatigue or lead to load-specific adaptations in muscle function (27,55,101).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Future research might also use randomized intervention designs to determine the extent to which strength preservation can be improved with training. Such research might identify exercise regimens that are most effective at improving tolerance to fatigue or lead to load-specific adaptations in muscle function (27,55,101).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…involves performing a maximal number of repetitions with a given absolute load regardless of changes in maximal strength (e.g., using 60% of pretraining 1RM at pre-and posttesting) [14]. In contrast, relative muscular endurance involves an individual performing a maximal number of repetitions with a load corresponding to a specific relative intensity or percentage of the individual's current 1RM (e.g., using 60% of pretraining and posttraining 1RM at pre-and posttesting, respectively) [14]. In addition, muscular endurance has been measured in several other ways when using different types of testing (e.g., isometric, isokinetic), such as time to task failure or total work during repeated isokinetic contractions [15,16].…”
Section: Key Pointsmentioning
confidence: 99%
“…According to the size principle, motor units are recruited in an orderly manner from the smaller motor units (i.e., low threshold) to the larger motor units (i.e., high threshold) as required force increases or muscle fatigues [44]. Based on this, increases in strength following resistance training may require fewer motor units to lift an absolute submaximal load for the same number of repetitions, which may delay the involvement of larger motor units and reserve them to be recruited subsequently for sustaining the required force as fatigue develops [14,45]. This hypothesis is partially supported by Ploutz et al [45] who showed that less muscle was recruited to lift the same submaximal load in the untrained leg following 9 weeks of unilateral knee extension training [45], which may reserve larger motor units to recruited on and consequently allow for better performance on the absolute muscular endurance test in the untrained limb.…”
Section: Increases In Muscle Strength (Cross-education Of Strength)mentioning
confidence: 99%